Atypical Features Resembling Poorly Differentiated Thyroid Carcinoma Presenting Entirely within a Follicular Adenoma. (18th July 2018) - Ching, Daniel; Leslie, Connull
Abstract : Poorly differentiated thyroid carcinoma (PDTC) is rare and is usually widely invasive at presentation. Here we present an unusual case with a component meeting diagnostic criteria for PDTC by Turin consensus proposal arising within a follicular adenoma. A 44-year-old female was found to have an incidental right thyroid nodule that was suggestive of follicular neoplasm on FNA. Histological examination of hemithyroidectomy revealed an 11 mm focus with insular growth pattern, alteration in cell morphology, and high mitotic count meeting criteria for PDTC. In addition there were several regions showing trabecular architecture with increased mitotic activity but not meeting criteria for PDTC. The literature for such cases is sparse but suggests much better prognosis than conventional invasive PDTC, although a biological potential for aggressive behaviour may be possible.